The Role of Institutional Ownership in Reducing the Impact of Transfer Pricing and Capital Intensity on Tax Avoidance - Sitanggang, Tikkos; Karsam, Karsam; Solihin, Solihin (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to examine the effect of capital intensity and transfer pricing on tax avoidance, as well as the role of institutional ownership as a moderating variable in these relationships. The object of this study consists of companies in the mining sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. Based on purposive sampling, 50 companies were obtained as samples which produced 250 research data. Data analysis was conducted using moderated regression analysis with an interaction test approach. The results indicate that, partially, both capital intensity and transfer pricing do not have a significant effect on tax avoidance. However, simultaneously, these two variables have a significant influence on tax avoidance. Furthermore, the study finds that institutional ownership moderates the relationship between capital intensity and tax avoidance, indicating that institutional investors may strengthen or weaken this relationship through their monitoring role. On the other hand, institutional ownership does not moderate the relationship between transfer pricing and tax avoidance. This study offers important implications for corporate management, regulators, and investors to consider the interaction between internal factors when addressing and managing tax avoidance behavior.